ORGANIC COMPOSITE IN AROEIRA-VERMELHA SEEDLING PRODUCTION - CALDEIRA, Marcos Vinicius Winckler; ROSA, Guilherme Nunes da; FENILLI, Tatiele Anete Bergamo; HARBS, Rosita Maria Pamplona (Scientia Agraria, 2008)
The good seedling formation for forest stand toward wood production and mixed stands toward environment preservation and/or degraded land recuperation is related to substrate efficiency. The aim of this work was to evaluate organic composite influence in aroeira-vermelha (Schinus terebinthifolius Raddi) seedling production. The experiment was realized at Forest Garden of Gaspar/Regional University of Blumenau-SC (FURB). The structure of the experiment was Completely Randomized Design with 6 treatments and 25 repetitions, it means, each plant was considered one repetition. The results of the quality index about seedling production on 100% of organic composite, in general, presented the lower index, except for the MSPA/MSR (aerial dried mass/root dried mass) index. However, the relation h/D (height/root collar diameter) is the one that presented similar values at the seeding quality index for all the treatments used. The seedlings that were produced with high proportions of organic composite at substrate had a negative effect, both about root length and dry biomass root production.